A Theoretical Study of the Insertion of Atoms and Ions into Titanosilsequioxane (Ti-POSS) in Comparison with POSS - Yosuke Komagata; Takaaki Iimura; Nobuhiro Shima; Takako Kudo (International Journal of Polymer Science)
The insertion reaction of various guest species, such as rare gases (He, Ne, and Ar), cations of group 1 (Li+, Na+, and K+), and anions of group 17 (F− and Cl−) elements, into the Ti analogues of POSS (polyhedral oligomeric silsesquioxanes), Ti-POSS, [HTiO1.5]n ( and 10), has been investigated by ab initio molecular orbital and density functional methods. For each case, the properties of the exohedral and endohedral complexes and transition-state structure connecting them on the potential energy surface and energetics are discussed in comparison with the case of POSS. Furthermore, in order to understand the origin of the stability of these structures, the binding energy () and the energy barrier of the encapsulation are analyzed by an energy decomposition method. As a result, some similarities and differences between Ti-POSS and POSS were explored.